2010
DOI: 10.1002/cnm.1424
|View full text |Cite
|
Sign up to set email alerts
|

Computational hemodynamics framework for the analysis of cerebral aneurysms

Abstract: Assessing the risk of rupture of intracranial aneurysms is important for clinicians because the natural rupture risk can be exceeded by the small but significant risk carried by current treatments. To this end numerous investigators have used image-based computational fluid dynamics models to extract patient-specific hemodynamics information, but there is no consensus on which variables or hemodynamic characteristics are the most important. This paper describes a computational framework to study and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 35 publications
0
76
1
3
Order By: Relevance
“…14 Pulsatile CFD simulations were performed for 2 cardiac cycles, and the results are presented for the second cycle. The results of these CFD computations were postprocessed to calculate the following aneurysmal hemodynamic quantities: 15 1) inflow rate into the aneurysm, 2) flow velocity averaged over the aneurysm volume, 3) shear rate averaged over the aneurysm volume, and 4) wall shear stress averaged over the aneurysm surface. Subsequently, the reduction of these quantities from the prestenting configuration to each of the stented models was calculated, and the minimum, maximum, and mean of these changes over the cardiac cycle were computed and compared.…”
Section: Hemodynamics Modelsmentioning
confidence: 99%
“…14 Pulsatile CFD simulations were performed for 2 cardiac cycles, and the results are presented for the second cycle. The results of these CFD computations were postprocessed to calculate the following aneurysmal hemodynamic quantities: 15 1) inflow rate into the aneurysm, 2) flow velocity averaged over the aneurysm volume, 3) shear rate averaged over the aneurysm volume, and 4) wall shear stress averaged over the aneurysm surface. Subsequently, the reduction of these quantities from the prestenting configuration to each of the stented models was calculated, and the minimum, maximum, and mean of these changes over the cardiac cycle were computed and compared.…”
Section: Hemodynamics Modelsmentioning
confidence: 99%
“…Algorithm 1 -Edge-by-edge matrix-vector product It is known that iterative Krylov solvers such as CG are very efficient at minimizing errors associated with higher frequency modes but can be rather slow for lower frequency ones (Aubry et al, 2008;Frank and Vuik, 2001;Löhner et al, 2011;Nicolaides, 1987;Vermolen et al, 2002), which in other words translates as the smaller the spectral condition number, that is, the ratio between the largest and smallest eigenvalues of the matrix, the faster convergence will be. The use of deflation aims to accelerate solution convergence by reducing the spectral condition number in comparison with the original system Mut, 2008), with Nicolaides (1987) presenting its mathematical proof, later discussed again by Frank and Vuik (2001). For a generic system of linear equations A·x ¼ b, given a deflation space W, of order n × m, rank m and m ≪ n, the projector P, of order n × n, mapping A −1 orthogonally onto W is:…”
Section: Hff 252mentioning
confidence: 99%
“…However, one can easily infer that if the smallest eigenvalue is too small, the number of iterations necessary may become less affordable, especially with larger systems of linear equations. Mut (2008) and then Aubry et al (2011) have shown that the adoption of deflation helps speed up the convergence of the solution by reducing the spectral condition number of the deflated system. The deflation space is then built in a way to remove from the solution the smallest eigenvalues, responsible for slowing convergence.…”
Section: Introductionmentioning
confidence: 97%
“…Despite these drawbacks, CFD has recently been used to associate intra-aneurysmal hemodynamics with rupture. 15 The enormous advancements in MR imaging technology in the past decade now allow direct measurement of intra-aneurys-mal flow by using 3D PC-MR imaging. 19 Moreover, the technique was validated against CFD in a real-size phantom.…”
mentioning
confidence: 99%